Percutaneous Transvenous Mitral Commissurotomy in patients with rheumatic heart disease: a hospital-based retrospective study - Mohd Firdaus, Mohd Al-Baqlish; Kelvin, Shenq Woei Siew; Zainal Abidin, Muhammad 'Adil; Mohd Said, Mohd Ridzuan; Hadi, Mohd Firdaus; Abdul Hafidz, Muhammad Imran; Ismail, Muhammad Dzafir; Arjan Singh, Ramesh Singh; Wan Ahmad, Wan Azman (Faculty of Medicine, Universiti Malaya, 2022)
Background: Percutaneous Transvenous Mitral Commissurotomy (PTMC) is a procedure of choice for the treatment of severe mitral stenosis. We aimed to describe our experiences on management of rheumatic heart disease with PTMC in Malaysia. Methods: Patients who underwent PTMC were traced through the electronic medical record of University Malaya Medical Centre. The patients detailed echocardiogram parameter pre-procedure, post-procedure and outcome were documented. Statistical analysis was performed using SPSS version on 18 for windows. Results: 11 patients were treated with PTMC in our centre with 90.9% (n=10) success rate. Subjects underwent PTMC were statistically significant associated with improved echocardiogram parameters as following: increase in mitral valve size (p=0.0058) from 0.89 ± 0.2 cm2 (pre) to 1.4 ± 0.4 cm2 (post); reduction in mean pressure gradient across mitral valve (p=0.0283) from 11.5 ± 4.9 mmHg (pre) to 6.9 ± 3.5 mmHg (post); and reduction (p=0.0019) in elevated pulmonary artery systolic pressure from 65.7 ± 21.4 mmHg (pre) to 45.6 ± 10.0 mmHg (post). More than half (62.5%, n=5) of the subjects with favourable Wilkin score 8 or less achieved good outcome defined as post-PTMC mitral valve size ≥ 1.5 cm2 . All subjects with unfavourable Wilkin score of more than 8 only achieved sub-optimal post-PTMC mitral valve size ≤ 1.5 cm2 . Conclusion: Given the minimally invasive nature of PTMC with comparable excellent haemodynamic outcome to invasive vascular repair, PTMC should be the recommended first line therapy in mitral valve stenosis.